APPLICATION OF VIDEO-BASED PROJECT LEARNING MODEL IN CIVIC EDUCATION COURSES - Minan, Muh. Zainul; Murdiono, Mukhamad; Astuti, Widya (Ridwan Institute, 2024)
The purpose of this research is to analyze the level of student participation and perception in applying the project-based learning model, specifically through video projects, in the civic education course, to evaluate the implementation of this learning model in the course, and to identify the skills that can be developed through its application in the form of videos in civic education. The study used mixed methods during the even semester of 2022/2023 (February 8-May 8, 2023). The research was conducted within the S-1 English Language Study Program at FBSB UNY, focusing on the application of a video project in the Civic Education course. The research narrows down the problem into three main objectives: (1) to analyze students' level of participation and the perception in application of the learning model to be applied in the civil education course; (2) to evaluate and identify skills that need to be developed in the use of the video in the curriculum. The results show that students' perceptions of the implementation using the video are very good with a percentage of 33% and good with the percentage of 60%. Students' perception of the development of skills in editing videos, teamwork (collaboration), problem solving (problem solving), speaking in front of the camera, and time management were also very good. This study provides insights into students' perceived benefits of using the model and the specific skills cultivated, such as creativity, collaboration, and digital literacy.